0087 Team Work And Attitudes To Ipl In Students Undertaking Interprofessional Simulation. (1st November 2014) - Roberts, Martin; Gale, Thomas; Endacott, Ruth; O'Connor, Anita
Abstract : Background: Interprofessional learning (IPL) can improve attitudes and awareness of other professionals' roles and may improve patient outcomes. Simulation is increasingly used for IPL and specific learning outcomes have been developed. This study aimed to measure undergraduates' attitudes to IPL, before and after, and team performance during, interprofessional simulation sessions. Methodology: Final year students (50 medical, 47 nursing), in groups of 7 to 12, completed the KidSIM ATTITUDES tool 1 before and after participating in a simulation session. Groups were divided into two mixed (medical/nursing) teams. One team undertook a 20 min scenario while the second team observed and scored their performance using the Team Emergency Assessment Measure (TEAM). 2 These roles were reversed for the second scenario. Reliability of both instruments was assessed by Cronbach's Alpha. We assessed pre-post changes in ATTITUDES scores using paired-sample tests. The association of student demographic factors with ATTITUDES score changes and TEAM ratings was investigated using ANOVA. Results: The ATTITUDES scale showed good reliability (Cronbach's α = 0.92). Total ATTITUDES scores showed a significant pre-post increase (paired t-test, p = 0.020) as did 25 of the 30 items (Wilcoxon rank sum test, p < 0.05). Total score increase was greater for those without prior team based learning experience (p = 0.011) and for White and Asian students (p = 0.007, p = 0.003) but did not vary with students' course, gender, prior IPL experience or session attended. Reliability of the TEAM score within small-group scenarios was moderate to good (Cronbach's α = 0.57–0.92). TEAM global score was unrelated to students' course, gender, ethnicity and age but was significantly lower in the first of the two scenarios (p = 0.001). Conclusions and recommendations: Simulation-based interprofessional education improved attitudes to IPL in final year nursing and medical students. Observing and rating peers may improve students' teamwork skills. Funded through a Collaborative Teaching Development Grant awarded by the Higher Education Academy. References: Sigalet et al . The KidSIM ATTITUDES questionnaire provides a reliable and construct valid measure of student perceptions of and attitudes toward IPE, teamwork, and simulation as a learning modality. Sim Healthcare 2012;7:353–358 Cooper et al . Team Emergency Assessment Measure (TEAM) is a reliable and valid instrument designed to measure emergency resuscitation team performance. Resuscitation 2010;81(4):446–52 Cronbach L. Coefficient alpha and the internal structure of tests. Psychometrika 1951;16:297–334